(3GdhLjR aj GdJaSjQs - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj GdfjSGHhQj , J (B468 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdcQje CeG HYO aEf dcd ReGf fThQkG s
(3BNQgG (B:s
(3hef TQ GdfGS dCfg CeQ Gf jSJYjP ef TQ GdLf s
(3GdfSNI HgG MhGTs
(3GdhQbJGf GdCNQJGf HNW MOjKs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ (B((3JaSjQ (B32) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs